Prisons and Religion in the Americas. Issue 12 (December 2013) - Graber, Jennifer
Abstract Since the 1970s and Michel Foucault's work discipline and power, scholars of religion in the Americas have looked to prisons to track changing ideas about human behavior, wrongdoing and reconciliation, social organization, and citizenship. This article provides a brief transatlantic history of the prison and scholarship on prisons and religion. It surveys work by historians, sociologists and anthropologists, and theologians and ethicists. It shows that religions have served as not only the material from which societies construct their disciplinary forms but also a resource upon which individuals draw when labeled criminal and communities invoke when seeking reform.